Impact of isovalent and aliovalent substitution on the mechanical and thermal properties of Gd2Zr2O7 - S. Zhang (Nature Portfolio, 2017)
Abstract In this study, a density functional theory method is employed to investigate the effects of isovalent and aliovalent substitution of Sm3+ on the phase stability, thermo-physical properties and electronic structure of Gd2Zr2O7. It is shown that the isovalent substitution of Sm3+ for Gd3+ results in the formation of Gd2Zr2O7-Sm2Zr2O7 solid solution, which retains the pyrochlore structure and has slight effects on the elastic moduli, ductility, Debye temperature and band gap of Gd2Zr2O7. As for the aliovalent substitution of Sm3+ for Zr4+ site, a pyrochlore-to-defect fluorite structural transition is induced, and the mechanical, thermal properties and electronic structures are influenced significantly. As compared with the Gd2Zr2O7, the resulted Gd2SmyZr2-yO7 compositions have much smaller elastic moduli, better ductility and smaller Debye temperature. Especially, an amount of electrons distribute on the fermi level and they are expected to have larger thermal conductivity than Gd2Zr2O7. This study suggests an alternative way to engineer the thermo-physical properties of Gd2Zr2O7 and will be beneficial for its applications under stress and high temperature.